Implementasi Pendidikan Karakter dan Budi Pekerti Peserta Didik - Qurbi, Abdullah; Diswantika, Noviana; Putri, Edhitiya (Lentera: Jurnal Ilmiah Kependidikan, 2021)
The current crisis in character education among students and the need for its implementation to address moral and behavioral problems are highlighted. This article also emphasizes the importance of character education in shaping the younger generation and the role of various stakeholders, including parents and teachers, in its implementation. The article describes the methods and goals of character education, as well as the implementation of character education in formal educational institutions. It also outlines the goals of character education in schools and its significance in shaping the behavior, attitudes, and personalities of students. This provides a comprehensive overview of the concept of character education and its significance in the Indonesian educational context. It discusses various definitions of character, the formation of character, and the goals and essence of character education in formal educational institutions. The article also emphasizes the importance of character education in shaping the behavior, attitudes, and personalities of students, as well as the role of various stakeholders in its implementation.